ASSESMENT OF THE ROLE OF STAKEHOLDERS IN THE MANAGEMENT OF BORDER INSECURITY USING AHP. A CASE STUDY OF GURIN-FOFURE, ADAMAWA STATE. - JOLLY P. M; MUAZU H. G. (International Studies Journal)
Despite the mechanisms put in place to address border insecurity, the challenge still exists on the global scale, which is more pronounced at both regional and local levels. Thus, the study assessed the role of stakeholders in managing border insecurity in Gurin Fufore Local Government Area of Adamawa State. The study highlighted the factors responsible for border insecurity, the role of stakeholders on border insecurity through the measures put in place by the stakeholders and the weight for ranking these roles for managing border insecurity using Group AHP. Delphi method was employed in the selection of participants for the study in the areas affected by border insecurity based on the knowledge of the population and the purpose of the studywith the sample size of 385. This was done in order to select stakeholders which are Police, Custom, Immigration, Army, Community leader and Youth leader in the bordering community who offered reasonable information to the research work. Analytical Hierarchy Process (AHP) was used to analysed the data and arithmetic mean was used to aggregate the relative weights for all the responses of each stakeholder and arrive at the final aggregated weights for each criterion of all the stakeholders. From the study,measure used to manage border insecurity are in these order: routine patrol on border areas (C7) is ranked 1st as the most effective tool, ensuring foreigners have their valid document (C6) is ranked 2nd, Synergy with government security agents (C4) is ranked 3rd, fixed surveillance (C8) is ranked 4th, effective guard and patrol by Pulako (C3) is ranked 5th, investigation (C9) is ranked 6th, addressing the Youth through town hall meetings (C7) is ranked 7th, effective guard and patrol by Vigilantes (C1) is ranked 8th and effective guard and patrol by Local Hunters (C2) is ranked 9th as the least effective. We discovered that some vital means of managing border insecurity such as effective guard and patrol by vigilantes, effective guard and patrol by local hunters, effective guard and patrol by pulako, addressing the youth through town hall meetings weren’t put to play. Hence, stakeholders should make effective use of these neglected measures in handling border insecurity as they play vital roles in managing border insecurity.